1989
DOI: 10.4141/cjss89-051
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tillage Reduction and Fertilizer on Soil Macro- And Microaggregation

Abstract: (Mazurak 1950) and aggregation index (AI) (Dobranski et al. 1975; MacRae and Mehuys 1987) were then calculated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 25 publications
1
9
1
Order By: Relevance
“…2). However, unlike those found in southern Ontario (Yang and Kay, 2001) and Quebec (Weill et al, 1989), ours results revealed that CP does not significantly raise soil organic carbon in the 0-20 cm layer compared to MP (Fig. 2).…”
Section: Soil Tillagecontrasting
confidence: 99%
See 2 more Smart Citations
“…2). However, unlike those found in southern Ontario (Yang and Kay, 2001) and Quebec (Weill et al, 1989), ours results revealed that CP does not significantly raise soil organic carbon in the 0-20 cm layer compared to MP (Fig. 2).…”
Section: Soil Tillagecontrasting
confidence: 99%
“…As Angers et al (1993) and Weill et al (1989) found earlier in eastern Canada, compared to MP, CP does not significantly affect mean weight diameter compared to MP after four years of soil tillage treatments. However, as our study showed, CP keeps more stable aggregates and greater mean weight diameters after eight years and differences even increase after twelve years (Fig.…”
Section: Soil Tillagesupporting
confidence: 51%
See 1 more Smart Citation
“…l). Angers and Mehuys (1988) and Perthis site for 5 yr prior to the initiation of the fect et al (1990) Weill et al (1989) and MWD was shown for each tillage treatment Raimbault and Vyn (l9l) also found little (Fig. a) Smettem et al (1992) also recently observed that aggregate disruption from the escape of compressed air (slaking) was found to have less effect on aggregates from soils under direct drill than from soils under conventional cultivation.…”
Section: Restjlts and Discussionmentioning
confidence: 95%
“…Under no-till practices crop residues are left on soil surface as mulch. Several studies have shown that this practices improve soil aggregation thus reduce soil organic matter and nutrients losses that result from tillage ( Havlin et al, 1990;Carter., 1992;Weill et., 1989 ).Loamy sand floodplain soils of Onwu in northern senatorial district of cross river state, Nigeria are characterized by high dispersibility, a factor that enhances susceptibility of tilled soils to aggregate disruption, surface crusting, poor infiltration and erosion ( Miller and Baharuddin, 1986 ). In tropical climate, these factors can contribute to rapid losses of soil organic matter and a decline in the productivity of agricultural soils ( Gidden, 1957;Bruce et al, 1990b;Sanchez et al, 1989 ).…”
Section: Introductionmentioning
confidence: 99%